A comparison of three conducted electrical weapons in a surrogate swine cardiac safety model. (January 2021) - Dawes, Donald M.; Ho, Jeffrey D.; Halperin, Henry R.; Fink, Sarah J.; Driver, Brian E.; Klein, Lauren R.
Abstract: We used a previously described methodology in a swine model to compare the relative cardiac safety of the Axon T7 Conducted Electrical Weapon (CEW), released in October of 2018, to two prior generations of Axon CEWs to include the X2 and the X26E. A total of 5 swine (252 total CEW exposures) were tested by alternating the three weapons at each chest exposure location. Our testing, using systemic hypotension as the quantitative surrogate for cardiac capture, demonstrated that the T7 and X2 were not statistically different. Both were superior, in terms of reduced hypotension during exposure, to the X26E. This study is important as it demonstrates that the newly released weapon is non-inferior to the X2 and superior to the X26E using this surrogate safety model. It is also important because it is the first study to examine the cardiac effects of simultaneous multi-bay exposures. Our prior study compared the X2 to the X26E but examined only single bay exposures from the X2. Lastly, we feel we have improved the methodology for studying the comparative cardiac effects of CEWs. Highlights: The proximity of the heart to the probe is the major determinant of CEW cardiac effect rather than a pathway. arterial line measurements may be the best quantitative objective data during exposures. The T7 and X2 were not statistically different in their ability to cause hypotensive cardiac capture. Both the T7 and X2 were superior to the X26E in that they caused less hypotensive capture. Our model appears to be a valuable model for studying the comparative cardiac effects of CEWs.